Usefulness of Cell‐Free Human Telomerase Reverse Transcriptase Mutant DNA Quantification in Blood for Predicting Hepatocellular Carcinoma Treatment Efficacy. Issue 11 (28th July 2021) - Muraoka, Masaru; Maekawa, Shinya; Katoh, Ryo; Komiyama, Yasuyuki; Nakakuki, Natsuko; Takada, Hitomi; Matsuda, Shuya; Suzuki, Yuichiro; Sato, Mitsuaki; Tatsumi, Akihisa; Miura, Mika; Amemiya, Fumitake; et al.
Abstract : Although the usefulness of liquid biopsy as a biomarker in the treatment of hepatocellular carcinoma (HCC) has been suggested, its usefulness in transcatheter arterial chemoembolization (TACE) or tyrosine kinase inhibitor (TKI) therapies has not been reported in detail. In this study, we investigated the clinical value of a cell‐free (cf)DNA quantification system targeting the human telomerase reverse transcriptase ( hTERT ) promoter mutation in advanced HCC treatment. Plasma from 67 patients with advanced HCC, treated with TACE and TKI, was used for extraction of cfDNA. We defined cfDNA with the hTERT promoter C228T mutation as circulating mutant DNA (mutant DNA) and without the mutation as circulating wild‐type DNA (wild‐type DNA). We analyzed the changes in mutant and wild‐type DNA levels during HCC treatment and examined the relationship between changes in the cfDNA level and the clinical course. Mutant DNA was detected in 73.1% (49/67) of the patients during HCC treatment. In univariate analysis, factors associated with detection of mutant DNA before treatment were the intrahepatic maximum tumor diameter ( P = 0.015) and protein induced by vitamin K absence (PIVKAII) ( P = 0.006). The degree of mutant DNA change after TACE was significantly correlated with tumor volume ( P < 0.001), reflecting the treated tumor volume. Responders with peak cfDNA levels within 1 week of TKI initiation had significantly better progression‐free survival than nonresponders ( P = 0.004). Conclusion: Changes in blood hTERT promoter mutant DNA levels during TACE or TKI treatment indirectly reflect the amount of HCCs and are useful for predicting long‐term treatment responses. Abstract : The usefulness of liquid biopsy as a biomarker in the treatment of hepatocellular carcinoma (HCC) in transcatheter arterial chemoembolization (TACE) or tyrosine kinase inhibitor (TKI) therapies has been unclear. In this study, we showed that changes in blood hTERT promoter mutant DNA levels during TACE or TKI treatment reflect the amount of HCCs and are useful for predicting long‐term treatment responses.